The Development of The Model in Health Promotion to the Senior Citizens by the Local Wisdom and Community Participation of Banklang Municipality, Banklang Subdistrict, Sanpatong District, Chiang Mai Province - แปงศิริ, มุจลินท์ (Community and Social Development Journal, 2015)
This was an action research for the development of the model in health promotion to the senior citizens by the local wisdom and community participation of Banklang municipality, Banklang subdistrict, Sanpatong district, Chiang Mai province by the empowerment process. The amount of people in this research was the senior citizens in Banklang municipality, Sanpatong 66 attended development procedure for research. The tools that were used in the data collection, an assortment the community, community map, community history and in-depth interview, a tool that used in data saving in the empowerment process, model to record the meeting, model to record group conversations, model to record the observation, questionnaire, and in-depth interview. The method that were used in data storage of the empowerment process was to record all meeting including observation, group discussions and in-depth interview. The quantitative data were statistically analyzed for frequency, mean, standard deviation and compared the mean before and after the operation and the qualitative data were statistically analyzed for content analysis. Results of the study The addition of empowerment and community involvement help to build the power and health in oneself in the care of the aged and community had and interested to see the importance of operating on group meeting, participating in group activity gave the aged were born the awareness in health problem, the problem may be analyzed, the community would come together to seek and solve the problem found, being revitalized would bring good health and the ability of long life. The development of self-care behaviors of the elderly by the empowerment process, the average of all process were observed at a high level. The average of self-esteem to recognize the power of their own and self-care behaviors of the elderly behind the empowerment was higher than before the operation on all sides. It was concluded that this activity could help empower older people had better self-care behaviors.